Channel Angular Pressing of Annular Billets Made from Non-ferrous Metals - Afanasiy M. Ivanov; Semen S. Vaschenko (Current Approaches in Engineering Research and Technology Vol. 5, 2024)
The purpose of the study is to implement the channel angular pressing (CAP) method developed based on the invention. The diagram, general view, and details of the device produced based on the invention are presented. Examples of cold CAP of annular billets made from technical copper M4 and aluminum are given. Annular billets were subjected to CAP at room temperature with a device with the outlet and inlet channels diameters ratio D / d @ 1.14. Annular billets were loaded with a tubular punch by an Instron-1195 testing machine. Diagrams of the loading of annular billets are presented. The results on the mechanical properties under axial compression of annular samples made of metals in the initial state and after CAP are presented. Mechanical tests for axial compression of annular samples were carried out with an Instron-1195 testing machine at a constant loading rate of » 0.83·10-5 ms-1. An increase in the strength of metals as a result of CAP at room temperature was found.